Mobile Multicast Sender Support in PMIPv6 Domains with Base Multicast Deployment - Thomas Schmidt and Matthias Wählisch and Muhamma Omer Farooq (2011)
Multicast communication can be enabled in Proxy Mobile IPv6 domains by deploying MLD Proxy functions at Mobile Access Gateways, and multicast routing functions at Local Mobility Anchors. This document describes the support of mobile multicast senders in Proxy Mobile IPv6 domains that is provided by this base deployment scenario. Mobile sources remain agnostic of multicast mobility operations.